Moslund, S.P., Marcussen, M.K., Pedersen, M.K. (Eds.). (2020). How Literature Comes to Matter. Post-Anthropocentric Approaches to Fiction. Edinburgh University Press - Srinivas, Vedant (Journal of Posthumanism, 2023)
How Literature Comes to Matter offers a path-breaking look at how New Materialist/Posthumanist theory might contribute to literary reflections on the entangled relations between humans and more-than-human material realities. By establishing a link between fiction and post-anthropocentric theory, the book attempts to broaden the scope of how such theory(-ies) might be used to interrogate the presence and significance of the objective and the non-human in literature.